2022
DOI: 10.30867/pade.v4i1.810
|View full text |Cite
|
Sign up to set email alerts
|

Peningkatan pengetahuan dan sikap ibu untuk pencegahan stunting di Kabupaten Aceh Besar

Abstract: Stunting terjadi mulai dari dalam kandungan dan baru terlihat saat anak berusia dua tahun. Stunting disebabkan oleh tiga faktor yaitu faktor individu yang meliputi asupan makanan, berat badan lahir, dan keadaan kesehatan; faktor rumah tangga yang meliputi kualitas dan kuantitas makanan, sumber daya, pola asuh, dan faktor lingkungan seperti sosial ekonomi, layanan pendidikan dan layanan kesehatan. Kegiatan ini bertujuan untuk meningkatkan pengetahuan dan sikap ibu terhadap pencegahan stunting balita. Pengabdian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
8

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 4 publications
1
5
0
8
Order By: Relevance
“…Children with ages of 6-12 months and 12-23 months are at a higher risk of stunting than children with ages of 0-6 months. This finding is in line with that of other studies (Toma et al, 2023;Mulyani et al, 2022). A cohort study of children's growth and development in Bogor also found that the Z-score for height according to children's age tended to decrease as the children aged.…”
Section: Resultssupporting
confidence: 92%
“…Children with ages of 6-12 months and 12-23 months are at a higher risk of stunting than children with ages of 0-6 months. This finding is in line with that of other studies (Toma et al, 2023;Mulyani et al, 2022). A cohort study of children's growth and development in Bogor also found that the Z-score for height according to children's age tended to decrease as the children aged.…”
Section: Resultssupporting
confidence: 92%
“…Several studies have shown the effectiveness of leaflet media in increasing knowledge about stunting prevention. Nutrition education by using leaflets media have a significant effect on increasing mothers' knowledge and attitudes to prevent stunting in Gurah village, Aceh, Indonesia (Mulyani, et al, 2022). Another study found that there was an effect of nutrition counseling using leaflets media towards knowledge among mothers who have stunted children in Bone, Indonesia (Nuheriana, et al, 2022).…”
Section: The Effectiveness Of Stunting Prevention Promotion To Improv...mentioning
confidence: 99%
“…Jika seorang remaja kurang gizi seperti berat badan yang rendah dan anemia, maka ketika remaja atau calon ibu tersebut hamil maka mereka akan cenderung akan melahirkan bayi dengan berat badan (BB) dan tinggi badan (TB) yang rendah yang akan berpotensi terjadinya stunting. Untuk itu, maka focus penanganan stunting saat ini harus melibatkan remaja agar remaja tersebut Ketika menikah dan siap hamil akan melahirkan bayi yang sehat dengan BB dan TB yang sesuai 11,12 .…”
Section: Pendahuluanunclassified